Pengaruh Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Pegawai (Studi Kasus Pada Koperasi Unit Desa Pakis Kabupaten Malang) - Wahyu Dwi Agustin; Eka Farida; Afi Rachmat Slamet (UNIVERSITAS ISLAM MALANG, 2022)
Abstract Based on the research carried out with the aim of knowing and analyzing the influence of leadership and work motivation on the performance of the case study employees at the Pakis Village Unit Cooperative. This research belongs to the type of quantitative descriptive research. The method used is multiple linear regression. The sampling technique used a saturated sample, namely all 36 samples of the Pakis Village Unit Cooperative employees. The sampling technique used in this study is saturated sampling where the determination of the sample when all members of the population are used as samples. To solve the problem in this study using SPSS assistance with validity test, reliability test, normality test, multiple linear regression analysis, multicollinearity test, heteroscedasticity test, f test, and t test. From this study, it was found that the variables of leadership, work motivation and employee performance had a positive and significant effect simultaneously on employee performance, partially the leadership variable had a positive and significant effect on employee performance, while the motivation variable had a positive and significant effect on employee performance. Keywords: Leadership, Work Motivation, Employee Performance